Species sorting and mass effect along forest succession: Evidence from taxonomic, functional, and phylogenetic diversity of amphibian communities. Issue 9 (8th April 2019) - Hernández‐Ordóñez, Omar; Santos, Bráulio A.; Pyron, Robert Alexander; Arroyo‐Rodríguez, Víctor; Urbina‐Cardona, J. Nicolás; Martínez‐Ramos, Miguel; Parra‐Olea, Gabriela; Reynoso, Víctor Hugo
Abstract: Species recovery after forest disturbance is a highly studied topic in the tropics, but considerable debate remains on the role of secondary forests as biodiversity repositories, especially regarding the functional and phylogenetic dimensions of biodiversity. Also, studies generally overlook how alpha and beta diversities interact to produce gamma diversity along successional gradients. We used a metacommunity approach to assess how species sorting (i.e., environmental filtering) and mass effect (i.e., source‐sink dynamics) affect 14 complementary metrics of amphibian taxonomic, functional, and phylogenetic diversity along a successional gradient in southern Mexico. As amphibians have narrow environmental tolerances and low dispersal capabilities, we expected that species sorting may be relatively more important than mass effect in structuring amphibian communities. Between 2010 and 2012, we sampled frogs, salamanders, and caecilians in 23 communities distributed in four successional stages: young (2–5 years old) and intermediate (13–28 years old) secondary forests, old‐growth forest fragments, and old‐growth continuous forest. We assessed 15 ecologically relevant functional traits per species and used a time‐calibrated molecular phylogeny. We recorded 1, 672 individuals belonging to 30 species and 11 families. Supporting our expectations from the species sorting perspective, from the poorest (younger forests) to the best quality (continuous forest) scenarios, we observed (a) an increase in alpha diversity regardless of species abundances; (b) a clear taxonomic segregation across successional stages; (c) an increase in functional richness and dispersion; (d) an increase in mean phylogenetic distance and nearest taxon index; and (e) a reduction in mean nearest taxon distance. However, 10 species occurred in all successional stages, resulting in relatively low beta diversity. This supports a mass effect, where interpatch migrations contribute to prevent local extinctions and increase compositional similarity at the regional scale. Our findings indicate that amphibian metacommunities along forest successional gradients are mainly structured by species sorting, but mass effects may also play a role if high levels of forest cover are conserved in the region. In fact, secondary forests and forest fragments can potentially safeguard different aspects of amphibian diversity, but their long‐term conservation value requires preventing additional deforestation. Abstract : Taxonomic, functional, and phylogenetic amphibian diversity along a secondary forest successional gradient indicates an increase in alpha species diversity regardless of species abundances, a clear taxonomic segregation across successional stages, an increase in functional richness and dispersion, an increase in mean phylogenetic distance and nearest taxon index, and a reduction in mean nearest taxon distance. This suggests that amphibian metacommunities along successional gradients are mainly structured by species sorting, but mass effects may also play a role if high levels of forest cover are conserved. Secondary forests and small forest fragments can potentially safeguard different aspects of amphibian diversity, but their long‐term conservation value requires preventing additional land‐use changes.